Toxicity of acaricides to kanzawa spider mite Tetranychus kanzawai Kishida (Acari: Tetranychidae) - Jerzon G. Villacencio (Annals of Tropical Research)
Kanzawa spider mites Tetranychus kanzawai, are among the most widespread and serious pests that infest economically important crops such as cassava. It is important to screen the toxicity of the available agrochemicals with acaricidal effects because chemical control remains an integral part in the management of these pests. This study presents the results of laboratory-based experiments that examined how T. kanzawai responded to six acaricides, namely abamectin, emamectin benzoate, fenpyroximate, hexythiazox, spirotetramat, and chlorfenapyr through leaf disk assay. Diluted concentrations of each of the six acaricides were prepared at 0.0001, 0.001, 0.01, 0.1, 1, 10, 100, and 1000mg of active ingredient per liter of solution. The study revealed that among the six registered acaricides in the Philippines, fenpyroximate has the most potent toxic effects on the mites' eggs, but it shows lower toxicity towards the adults. Conversely, hexythiazox exhibits high toxicity to adults but, based on a previous study, does not surpass the toxicity of the biorational alternatives abamectin and emamectin benzoate. The results of this study contribute to greater evidence that some acaricides are ineffective against T. kanzawai. The study revealed that hexythiazox and fenpyroximate can alternatively be used in managing T. kanzawai. Considering cassava's importance as a vital root crop, educating farmers on the responsible use of these acaricides is vital for the effective management of T. kanzawai , thereby ensuring cassava crop yield preservation and food security. These efforts can contribute to the development of targeted and sustainable pest management strategies for T. kanzawai in cassava cultivation.